Upaya Meningkatkan Rasa Percaya Diri Melalui Kegiatan Bermain Peran Anak Usia 4-5 Tahun - Khotimah, Kholisfatul; Sandra Barata, Mahendra Aswit; Kharismawati, Indah (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This study aims to enhance the self-confidence of early childhood students through the implementation of role-playing methods at RA Miftahul Hidayah, Panti District, Jember Regency. The research method used is Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The research subjects were 20 children aged 4-5 years. Results in Cycle I indicated that 55% of the children showed increased self-confidence, but this result did not meet the target of 75% success. In Cycle II, improvements were made through individualized guidance and more varied role-playing scenarios. As a result, 75% of the children showed significant self-confidence enhancement. Thus, role-playing methods have proven effective in supporting the socio-emotional development of children and can be widely implemented in early childhood education settings.